The Construction of P.Bodmer viii and the Bodmer “Composite” or “Miscellaneous” Codex - Nongbri, Brent (Novum Testamentum, 2016)
The construction of the so-called Bodmer Composite or Miscellaneous codex has been an ongoing problem since the publication of its constituent parts began in the 1950s. A recent inspection of high resolution digital images of P.Bodmer viii shows compellingly that this portion of the codex had more than one phase of use, was originally part of a separate codex, and was only later removed and joined to the other sections of the Bodmer “composite” codex. The New Testament manuscript known as P72 (P.Bodmer vii + P.Bodmer viii) is thus a codicological unity only in a secondary sense.